How to handle a Highlander - Wine, Mary (Sourcebooks Casablanca, 2013)
Moira Fraser vows to marry the elderly Laird Achaius Morris to avoid inciting another clan war, but she must resist the charms of the stubborn Gahan Sutherland, who will stop at nothing to foil Moira's wedding.